2019
DOI: 10.3390/electronics8020252
|View full text |Cite
|
Sign up to set email alerts
|

City Marathon Active Timing System Using Bluetooth Low Energy Technology

Abstract: This study proposes and implements city marathon timing technology using Bluetooth Low-Energy (BLE) communication technology. This study also performs a prevalidation of the athletes’ physiological sensory data that is sent out by the same timing system—the BLE active communication technology. In order to verify the timing and positioning technology, 621 K records of static measurement of the Received Signal Strength Indicator (RSSI) were first collected. The trend of the RSSI between the location and the BLE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Another technology that can be used for the gate crossing problem is Bluetooth low-energy technology (BLE). Sun et al [9] studied the accuracy of this technology for gate crossing. They used a high-speed camera to quantify the accuracy of the BLE technology in different running scenarios (BLE tags worn at different locations and emitting at different signal strengths) and found that the timing error is always less than 156 milliseconds.…”
Section: Related Work 21 Sensor-based Tracking and Timingmentioning
confidence: 99%
“…Another technology that can be used for the gate crossing problem is Bluetooth low-energy technology (BLE). Sun et al [9] studied the accuracy of this technology for gate crossing. They used a high-speed camera to quantify the accuracy of the BLE technology in different running scenarios (BLE tags worn at different locations and emitting at different signal strengths) and found that the timing error is always less than 156 milliseconds.…”
Section: Related Work 21 Sensor-based Tracking and Timingmentioning
confidence: 99%
“…The research and analysis of the successful marathon in characteristic cities reveal that the urban marathon can reflect the host city's cultural heritage and cultural connotation. The successful holding of this kind of competition can significantly improve the city's cultural influence and fully present the city's strong cultural and historical characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, device-based solutions require that each person carries a device on, which can be identified through a monitoring network. The most common devices are RFID (radio frequency identification) Tags [12,13], GPS (global positioning system) Tracker [14,15], Cellular Phones [16][17][18], BLE (Bluetooth low energy) Beacons [19][20][21] and Wi-Fi devices (tablet, portable, cellular, etc.) [22].…”
Section: Introductionmentioning
confidence: 99%